Moral formation and the virtuous life - Blowers, Paul M. (Ad fontes early Christian sources, 2019)
The anatomy and scope of repentance -- Resisting worldly powers and renouncing worldly evils -- Christianity as a rule of life -- Divine paideia and the quest for moral wisdom -- Biblical narrative, hagiography, and moral mimesis -- Sacraments, liturgy, and moral formation -- Habituating virtues and eradicating vices -- Love : beginning and end of the Christian virtues